Keabsahan Kontrak yang dibuat Melalui Artificial Intelligence (AI) dalam Perspektif Hukum Perdata Indonesia - Fanisa Asyatilah Rusli; Dhiaul Azkiya; Putri Zahra Maulidina; Fajar Caesar; Neng Sri Suryati (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The development of Artificial Intelligence (AI) has significantly influenced the formation of contracts in civil law, particularly through the automation of clause drafting, risk analysis, and the standardization of contractual documents. The use of AI in contract drafting raises complex legal issues, especially concerning the validity of agreements and the attribution of legal liability in the event of default. This study aims to analyze the validity of contracts created through Artificial Intelligence from the perspective of Indonesian civil law and to examine models of legal liability in AI-based contracts. This research employs a normative legal method with statutory and conceptual approaches, examining the provisions of the Indonesian Civil Code, particularly Article 1320, as well as legal doctrines and scholarly perspectives on digital contracts and AI. The findings indicate that AI-based contracts are, in principle, legally valid as long as they fulfill the requirements of a valid agreement, namely the consent of the parties, legal capacity, a specific object, and a lawful cause. Artificial Intelligence cannot be positioned as a legal subject because it lacks intent, consciousness, and the capacity to bear rights and obligations, and therefore functions solely as a technological tool. Consequently, legal intent and liability remain attached to the human or legal entity that uses, controls, or benefits from AI. This study also emphasizes that the primary challenge of AI-based contracts lies in the absence of specific legal regulations governing the allocation of liability among AI users, system providers, and developers, particularly when default occurs due to algorithmic errors or system failures. Therefore, clearer, adaptive, and comprehensive regulations are required to ensure legal certainty, protect the parties involved, and maintain a balance between technological innovation and the principles of justice in AI-based contractual practices in Indonesia.